An improved GaN P-HEMT small-signal equivalent circuit with its parameter extraction. (June 2021) - Zhang, Jincan; Wang, Shaowei; Liu, Min; Liu, Bo; Wang, Jinchan
Abstract: an improved small-signal model for the GaN pseudomorphic high electron mobility transistor (P-HEMT) process is proposed in this paper. Experimental studies have found that a high positive bias voltage usually damages or destroys the Schottky grid. In order to solve this problem, a method of extracting parasitic inductance and parasitic resistance using low gate bias voltage technology is proposed. Experimental research found that the parasitic circuit parameters will change with the bias voltage. New intrinsic resistance ( R L ) and intrinsic inductance ( L ds ) are introduced into the intrinsic equivalent circuit to suppress its bias dependence to solve this problem. At the same time, it is found that there is a time delay phenomenon in the parasitic parameter model, so the RC network ( R pds and C pds, R pgd and C pgd ) is introduced to represent this phenomenon. It is successfully applied to model a GaN P-HEMT. Excellent agreement between measured and modeled S -parameters is obtained from 0.5 to 20.5 GHz.